All the President's men revisited [videorecording (DVD)]. - Hoffman, Dustin, 1937-; Redford, Robert; Woodward, Bob, 1943-; Bernstein, Carl, 1944-; Stewart, Jon, 1962- (Discovery Communications LLC, 2013)
Watergate comes to life with riveting archival footage, shocking Oval Office recordings, and compelling new interviews with those who perpetuated the crimes, those who pursued them, and those who portrayed them. The presentation unravels the story that began with a third-rate burglary attempt and escalated into the first and only Presidential resignation in American history. A remarkable cast tells the tale, including Robert Redford, Bob Woodward, Carl Bernstein, Dustin Hoffman, and Jon Stewart.